2002
DOI: 10.1073/pnas.052028699
|View full text |Cite
|
Sign up to set email alerts
|

A screen for dominant mutations applied to components in the Drosophila EGF-R pathway

Abstract: The Drosophila epidermal growth factor receptor (EGF-R) controls many critical cell fate choices throughout development. Several proteins collaborate to promote localized EGF-R activation, such as Star and Rhomboid (Rho), which act sequentially to ensure the maturation and processing of inactive membrane-bound EGF ligands. To gain insights into the mechanisms underlying Rho and Star function, we developed a mutagenesis scheme to isolate novel overexpression activity (NOVA) alleles. In the case of rho, we isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…Interestingly, the mutations in clv1-1, clv1-2, and clv1-9 lie within or close to the activation loop in the kinase domain (Torii and Clark, 2000). Some mutations in animals are comparable to these: the EGFR DN3 mutation is located in domain VIb, and the bmpr2 mutation is located between domains VIb and VII (Zou and Niswander, 1996;Guichard et al, 2002;Rudarakanchana et al, 2002). Studies on bmpr2 showed that this dominant-negative mutant is not expressed at the plasma membrane but instead is retained in the endoplasmic reticulum (Rudarakanchana et al, 2002).…”
Section: Potential Mechanisms By Which Dominant-negative Clv1 Allelesmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the mutations in clv1-1, clv1-2, and clv1-9 lie within or close to the activation loop in the kinase domain (Torii and Clark, 2000). Some mutations in animals are comparable to these: the EGFR DN3 mutation is located in domain VIb, and the bmpr2 mutation is located between domains VIb and VII (Zou and Niswander, 1996;Guichard et al, 2002;Rudarakanchana et al, 2002). Studies on bmpr2 showed that this dominant-negative mutant is not expressed at the plasma membrane but instead is retained in the endoplasmic reticulum (Rudarakanchana et al, 2002).…”
Section: Potential Mechanisms By Which Dominant-negative Clv1 Allelesmentioning
confidence: 99%
“…Deletion of all or part of the cytoplasmic domain of the receptor-Tyr kinase epidermal growth factor receptors or other receptor-Tyr kinases results in dominant-negative mutations (Kashles et al, 1991;Chen et al, 1993;Prager et al, 1994;Guichard et al, 2002). The two CLV1 alleles that mimic this kind of mutation, clv1-6 and clv1-7, exhibit a weak phenotype similar to that of null alleles.…”
Section: Potential Mechanisms By Which Dominant-negative Clv1 Allelesmentioning
confidence: 99%
“…This approach has been used successfully for many Drosophila genes and is also being used to address the roles of genes involved in human disease. In a slight twist on this approach, one can also isolate alleles of the gene of interest (X) by directly mutagenizing the strain carrying the UAS-gene X responder (Guichard et al, 2002;Penton et al, 2002).…”
Section: A Genetic Tool For All Occasionsmentioning
confidence: 99%
“…The rationale of these experiments is straightforward: mutations affecting the same signalling pathway result in a similar phenotype and in general display genetic interactions. Thus, exhaustive genetic screens aimed to identify www.intechopen.com genes regulating embryonic segmentation in flies were instrumental to identify many components of the Notch, BMP, Hh and Wnt pathways (Nusslein-Volhard and Wieschaus, 1980), and genetic screens carried out in sensitized genetic backgrounds resulted in the identification of additional components of these pathways and also of the EGFR and InR pathways (Greaves et al, 1999;Rebay et al, 2000;Huang and Rubin, 2000;Guichard et al, 2002;Mahoney et al, 2006). More recently, mosaic screens in adult structures of the fly uncovered the SWH pathway, because of its contribution to the regulation of cell proliferation, competition and apoptosis (Cho et al, 2006;Tapon, 2007 Tyler et al, 2007).…”
Section: Drosophila As a Model Organism To Analyse The Genetic And Cementioning
confidence: 99%